Telomerase Activation to Reverse Immunosenescence in Elderly Patients With Acute Coronary Syndrome: Protocol for a Randomized Pilot Trial - Maier, Rebecca (JMIR Res Protoc, 2020)
BACKGROUND: Inflammation plays a key role in the pathophysiology of coronary heart disease (CHD) and its acute manifestation, acute coronary syndrome (ACS). Aging is associated with a decline of the immune system, a process known as immunosenescence. This is characterized by an increase in highly proinflammatory T cells that are involved in CHD progression, plaque destabilization, and myocardial ischemia–reperfusion injury. Telomere dysfunction has been implicated in immunosenescence of T lymphocytes. Telomerase is the enzyme responsible for maintaining telomeres during cell divisions. It has a protective effect on cells under oxidative stress and helps regulate flow-mediated dilation in microvasculature. OBJECTIVE: The TACTIC (Telomerase ACTivator to reverse Immunosenescence in Acute Coronary Syndrome) trial will investigate whether a telomerase activator, TA-65MD, can reduce the proportion of senescent T cells in patients with ACS with confirmed CHD. It will also assess the effect of TA-65MD on decreasing telomere shortening, reducing oxidative stress, and improving endothelial function. METHODS: The study was designed as a single-center, randomized, double-blind, parallel-group, placebo-controlled phase II trial. Recruitment started in January 2019. A total of 90 patients, aged 65 years or older, with treated ACS who have had CHD confirmed by angiography will be enrolled. They will be randomized to one of two groups: TA-65MD oral therapy (8 mg twice daily) or placebo taken for 12 months. The primary outcome is the effect on immunosenescence determined by a decrease in the proportion of CD8+ TEMRA (T effector memory cells re-expressing CD45RA [CD45 expressing exon A]) cells at 12 months. Secondary outcomes include leukocyte telomere length, endothelial function, cardiac function as measured by echocardiography and NT-proBNP (N-terminal fragment of the prohormone brain-type natriuretic peptide), systemic inflammation, oxidative stress, and telomerase activity. RESULTS: The study received National Health Service (NHS) ethics approval on August 9, 2018; Medicines and Healthcare products Regulatory Agency approval on October 19, 2018; and NHS Health Research Authority approval on October 22, 2018. The trial began recruiting participants in January 2019 and completed recruitment in March 2020; the trial is due to report results in 2021. CONCLUSIONS: This pilot trial in older patients with CHD will explore outcomes not previously investigated outside in vitro or preclinical models. The robust design ensures that bias has been minimized. Should the results indicate reduced frequency of immunosenescent CD8+ T cells as well as improvements in telomere length and endothelial function, we will plan a larger, multicenter trial in patients to determine if TA-65MD is beneficial in the treatment of CHD in elderly patients. TRIAL REGISTRATION: ISRCTN Registry ISRCTN16613292; http://www.isrctn.com/ISRCTN16613292 and European Union Drug Regulating Authorities Clinical Trials Database (EudraCT), European Union Clinical Trials Register 2017-002876-26; https://tinyurl.com/y4m2so8g INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/19456